Efektivitas Media Video Tutorial dalam Meningkatkan Keterampilan Menyetrika Pakaian Seragam Sekolah bagi Anak Disabilitas Intelektual Ringan - Maifajri, Resi; Rahmahtrisilvia, Rahmahtrisilvia (Al-DYAS, 2024)
This research aims to prove that video tutorial media is effective in improving school uniform ironing skills for children with mild intellectual disabilities. This research uses a quantitative approach using the Single Subject Research type with an A-B-A design. The subject of this research was 1 child with mild intellectual disabilities in Class VII SLB Muhammadiyah Pauh IX Padang . The child cannot yet iron school uniforms. Technique data collection used is test deed . Then the data is analyzed with visual analysis of the graphs used For assess the data in condition And between condition . On baseline conditions (A1) were obtained inclination stability on range stability 3 .75 , mean level 25, limit above 26.875, limit below 23.125 and percentage 100% stability . On condition intervention (B) is obtained range stability 12 .75 , mean level 73.33, limit above 79.705, limit below 66,955 and percentage stability 16.66%. Then on baseline condition (A2) range stability 13 .5 , mean level 87.75, limit above 94.25, limit below 80.75 and percentage stability 75%. Results from research that has been done obtained that the skill of ironing school uniforms increased after intervention with video tutorial media . From the results the show that Video tutorial media is effective in improving school uniform ironing skills.